Pendidikan Inklusif untuk Anak dengan Kebutuhan Kesehatan Khusus - Atien Nur Chamidah (JPK (Jurnal Pendidikan Khusus), 2010)
Children with special health care needs who have the chronic illness such as asthma, cancer, and hearth disease need a health care in the long time period.  Moreover, as a child they also need another service such as education that in many cases can't be accessed in an easy way due to their illness condition. Inclusive education comes up as a solution to deal with this problem. However, schools have to consider with some aspects that have to be prepared before they receive the children. Aspects of this condition include history of the illness, health care planning, team communication, school absence, and shool environment.